Catalytic synthesis of fatty acid methyl esters from Madhuca indica oil in supercritical methanol. (1st October 2018) - Lamba, Neha; Adhikari, Sangeeta; Modak, Jayant M.; Madras, Giridhar
Graphical abstract: Highlights: Different metal oxides were synthesized using solution combustion synthesis. FAMEs were obtained by integrated process in the presence of a catalyst. Eley-Rideal type mechanism was derived and pseudo first order kinetics was obtained. Effect of time, temperature and variation of fuel (combustion synthesis) was studied. MgO synthesized using ascorbic acid as a fuel was found to be most active catalyst. Abstract: Fatty acid methyl esters (FAMEs) that are used as biodiesel can be synthesized in supercritical methylating agents such as supercritical methanol. While the synthesis can be conducted both non-catalytically and catalytically, the synthesis in the presence of oxides is significantly faster. In this study, FAMEs were synthesized by transesterification of a non-edible oil (Mahua, Madhuca indica ) in supercritical methanol with a wide variety of oxides. The reaction was extensively studied with eleven different oxides, synthesized using the solution combustion method, as catalysts. In addition, the best two catalysts, namely MgO and Mn3 O4, were synthesized using four different fuels in the combustion synthesis. The catalytic effect of all these oxides was investigated and conversions ranging from 5% to 100% were obtained over the investigated range of temperature from 503 K to 583 K, and with reaction time varying between 2 min and 80 min. Among all the catalysts, MgO synthesized with ascorbic acid as the fuel for the solution combustion gave the best results. Therefore, this catalyst was chosen and the influence of operating temperature for the transesterification reaction (503–583 K) on the rate of the reaction was studied. A pseudo first order kinetic model was obtained based on the proposed Eley-Rideal reaction mechanism and, the rate constants were obtained. The rate constants varied between 1.61 × 10 −3  s −1 to 4.93 × 10 −3  s −1 with an activation energy of 36 kJ/mol and a pre-exponential factor of 9.33 s −1 . The rate constant obtained for the non-catalytic supercritical transesterification with oxide as catalyst was significantly higher than the rate constant of 9.9 × 10 −5  s −1 obtained for the non-catalytic reaction at 523 K. The activation energy for the catalyzed reaction (36 kJ/mol) was notably lower than the activation energy (75 kJ/mol) for the uncatalyzed reaction indicating the efficacy of the catalyst.